2008
DOI: 10.1590/s0100-46702008000400007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phenolic compounds and evaluation of antioxidant capacity of Campomanesia adamantium leaves

Abstract: Five flavanones and three chalcones were isolated from Campomanesia adamantium Berg. (Myrtaceae) leaves. The contents of these compounds were determined by HPLC. The phenolic contents were also determined. The monitoring of the antioxidant activity was carried out by inhibition of peroxidation using the linoleic acid system and radical-scavenging (DPPH). The plants were collected from 4 distinct cities of the Mato Grosso do Sul State, Brazil. The different samples exhibited a range of 4.67-232.35 mg/g chalcone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
1
32
0
5
Order By: Relevance
“…Some authors reported phenolic contents in leaves of other Myrtaceae species. Coutinho et al (2008) found a TPC of 7.2-21.2 mg GAE/g extract in Campomanesia adamantium. Salvador et al (2011) reported high values for Eugenia chlorophylla, Eugenia pyriformis, Myrcia laruotteana, and Myrcia obtecta (343.7-429.3 mg GAE/g extract).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some authors reported phenolic contents in leaves of other Myrtaceae species. Coutinho et al (2008) found a TPC of 7.2-21.2 mg GAE/g extract in Campomanesia adamantium. Salvador et al (2011) reported high values for Eugenia chlorophylla, Eugenia pyriformis, Myrcia laruotteana, and Myrcia obtecta (343.7-429.3 mg GAE/g extract).…”
Section: Discussionmentioning
confidence: 94%
“…The focus of antioxidant studies in the Myrtaceae family from Brazil has been on edible fruits (Marin et al, 2008;Rufino et al, 2009Rufino et al, , 2010Pereira et al, 2012) with few reports on leaves (Coutinho et al, 2008;Salvador et al, 2011). Thus, our results contribute valuable knowledge about the bioactive properties of native Myrtaceae species.…”
Section: Discussionmentioning
confidence: 99%
“…C. adamantium is a common species in Brazilian cerrado, and its anti-inflammatory, antidiarrheal, antiseptic, and antioxidant activities, reported by the native population, have been confirmed in previous studies (Ramos et al, 2007;Coutinho et al, 2008;Pascoal et al, 2011;Ferreira et al, 2013;de Souza et al, 2014). However, few studies on its mutagenic potential have been reported.…”
Section: Discussionmentioning
confidence: 74%
“…The fruit is commonly known as guavira, gabiroba, or guabiroba, and appears from September to December (Avidos and Ferreira, 2000). Species belonging to the Campomanesia genus have been shown to have medicinal properties, such as anti-inflammatory, antidiarrheal, antiseptic (Rodrigues and Carvalho, 2001;Brandelli et al, 2011;de Souza et al, 2014), and antioxidant activities (Ramos et al, 2007;Coutinho et al, 2008;Rufino et al, 2010;Pascoal et al, 2011), which are mainly attributed to the presence of phenolic compounds, flavonoids, chalcones, carotenoids, and vitamins.…”
Section: Introductionmentioning
confidence: 99%
“…When the biological activities of these organic extracts from C. adamantium were evaluated, they showed promising cytotoxic and antioxidant activities (RAMOS et al, 2007). COUTINHO et al, (2008a) isolated five flavanones and three chalcones from C. adamantium leaves using HPLC. Extracts were obtained from leaves of this species harvested in four cities in Mato Grosso do Sul State, Brazil, revealing different amounts of total phenolic compounds and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%